A Comparative Study on the Use of Paper-based and Digital Flashcards as Media to Learn Vocabulary at the First-grade Students of Senior High School in the Academic Year 2024/2025 - Hidayat, Azhari Wahyu; Sahuddin; Melani, Boenista Zulandha; Lestari, Yuni Budi (Journal of English Education Forum (JEEF), 2025)
This study aimed to compare the effectiveness of paper-based flashcards and digital flashcards as media for learning general vocabulary and to determine whether there was a significant difference between their use. This study was conducted at SMAN 1 Selong in the academic year 2024/2025 and aimed to compare the use of paper-based and digital flashcards as media in vocabulary learning to find out if there is a significant difference from the use of both. This study used quantitative research method with quasi-experimental research design. The research data was collected by giving pre-test and post-test to two sample classes consisting of 72 students with 36 students per class, namely class 10-1 (digital flashcards) and 10-9 (paper flashcards). After analyzing the data and testing the hypothesis using the Mann-Whitney test, the results obtained were Asymp. Sig. (2-Tailed) was 0,103 which was greater than > the probability value of 0,05 which means H0 is accepted and Ha is rejected. Indicating that there are no significant differences between the uses of paper flashcards and digital flashcards as media in vocabulary learning for first-grade students of SMAN 1 Selong in the academic year 2024/2025. Future research is encouraged to explore broader vocabulary coverage, including specialized vocabulary and other linguistic aspects such as word forms and usage. Additionally, educators are advised to enhance their teaching methods by integrating creative instructional strategies and effective learning media.